Ocena ryzyka demograficznego w ubezpieczeniach społecznych w Polsce i wybranych krajach UE - Balcerowicz-Szkutnik, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents a dynamic analysis of selected statistical parameters that characterize demographic risk for Poland and selected EU countries in connection with social insurance systems (particularly pension insurance). The analysis is preceded by a brief description of currently functioning pension systems in these countries. The summary focuses upon problems of proper functioning of these systems having their source in the change of population structure in the considered countries. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 26-34